Three-stage fermentation of the feed and the application on weaned piglets - Jiang, Dahai; Yang, Manqi; Xu, Jun; Deng, Liping; Hu, Cong; Zhang, Liangliang; Sun, Yunzhang; Jiang, Jianchun; Lu, Liming (Frontiers in Veterinary Science, 2023)
Numerous studies have demonstrated that soybean meal (SBM) contains high levels of anti-nutritional factors, which interrupt gastrointestinal homeostasis or metabolism normally of the weaned piglets. Here, the mixed probiotics, including Bacillus licheniformis (B. licheniformis, CGMCC 8147), Saccharomyces cerevisiae H11(S. cerevisiae H11) and Lactobacillus casei (L. casei, CGMCC 8149) were applied to the three-stage fermentation of functional feed. Our research investigated the optimum ratio of inoculation, optimal time of inoculation, combination of substrates, and nutritional value of the fermented feed. The optimal microbial combination was B. licheniformis: S. cerevisiae H11: L. casei = 2:2:1, inoculating at 0, 12 and 24 h, respectively. The results revealed that crude protein and acid-soluble protein were remarkably improved and had lower pH. Trypsin inhibitor, glycine and β-glycine were reduced by 79.86%, 77.18% and 69.29%, respectively. Moreover, animal trials further evaluated the growth-promoting effects of the fermented feed. It was noted that the average daily gain of weaned piglets was significantly higher, and the ratio of feed with weight, diarrhea incidence and mortality were lower significantly. The concentrations of serum immunoglobulin G(IgG), IgA, IgM, Complement C3 and interferon-γ (IFN-γ), and lysozyme activity were all increased. The relative abundance of fecal microbiota improved, especially lactobacillus, which increased the abundance of fecal dominant probiotics. Overall, the fermented feed may be conducive to the growth and health of weaned piglets by improving nutritional value, immunity properties, relative abundance of fecal microflora, and decreasing anti-nutritional factors of feed, thereby making them viable and usable feedstuffs for potential use in livestock industries.